Potential Sequencing Batch Reactor in Leachate Treatment for Organic and Nitrogen Removal Efficiency - Hariestya Viareco; Endi Adriansyah; Rifqi Sufra (Universitas Airlangga, 2023)
Introduction: Landfill wastewater or leachate has unique characteristics. Several conventional methods need a few treatment tanks to cover the treatment process. A Sequencing Batch Reactor (SBR) is a biological treatment method that uses a single tank with few-cycle phases. This study aims to determine the potential of a Sequencing Batch Reactor (SBR) that can be used to treat landfill leachate. Methods: A Sequencing Batch Reactor (SBR) was used in this study. The characteristics of leachate served as the basis for the design of the SBR reactor. The synthetic leachate was used to create the reactor feed based on the actual landfill leachate compositions. The reactor's influent and effluent were analyzed based on a few parameter changes, such as Suspended Solid (SS), Chemical Oxygen Demand (COD), ammonia nitrogen (NH3-N), and Total Kjeldahl Nitrogen (TKN). Results and Discussion: While the experiment was running, 84% of SS were removed, 88% of COD were removed, a -28% efficiency rate for NH3-N removal, and a -172% efficiency rate for TKN removal. After the withdrawal phase, the supernatant showed promising results with 99% COD removal, 97% SS removal, and 65% TKN removal. Unfortunately, the removal of NH3-N reaches -130%. It indicates insufficient concentrations of MLSS and SRT, as well as the presence of a eutrophication process. Conclusion: SBR shows a promising result for leachate treatment. Few changes in the cycling process were needed for further study, so the treatment process becomes optimal to reach its full potential.